Analyze the strategy of Islamic Education Institutions in implementing the Independent Curriculum: Analisis Strategi Lembaga Pendidikan Islam Di Tingkat Sekolah Menengah Pertama (SMP) Dalam Implementasi Kurikulum Merdeka - Magfiroh, Ainun; Nurdyansyah (Indonesian Journal of Innovation Studies, 2026)
General Background: The Merdeka Curriculum represents Indonesia’s initiative to improve national education by emphasizing character building, flexibility, and contextual learning. Specific Background: Islamic Educational Institutions (LPI) at the junior high school (SMP/MTs) level must integrate national educational standards with Islamic values and institutional quality management. Knowledge Gap: However, systematic literature syntheses analyzing how LPIs specifically execute quality management strategies and overcome implementation barriers at the secondary level remain scarce. Aims: This systematic literature review evaluates management strategies, learning development, and implementation challenges of the Merdeka Curriculum in junior high LPIs using the PRISMA framework. Results: Synthesis of primary studies reveals positive contributions toward fostering student critical thinking, independence, 4C soft skills, and Pancasila character development. Novelty: This study provides a structured framework detailing LPI quality management phases alongside specific operational constraints in Islamic secondary education. Implications: Stakeholders must enhance collaborative efforts, teacher training programs, digital media availability, and infrastructure to optimize curriculum execution. Key Findings Highlights Implementation of Merdeka Curriculum fosters student critical thinking, independence, soft skills, and Pancasila character. Quality management involves structured planning, lesson plan modifications, resource allocation, and supervision. Constraints include teacher readiness, limited digital infrastructure, insufficient training, and resource availability. Keywords : Merdeka Curriculum, Islamic Educational Institutions, Quality Management Strategy, Junior High School, Literature Review